2020
DOI: 10.1186/s12884-020-2746-0
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of pregnant women of reasons for late initiation of antenatal care: a qualitative interview study

Abstract: Background: Antenatal care serves as a key entry point for a pregnant woman to receive a broad range of services and should be initiated at the onset of pregnancy. The aim of the study was to understand the reasons for the late initiation of antenatal care by pregnant women in Nkwen Baptist Health Centre, Bamenda, Cameroon. Methods: The study applied purposive sampling to recruit eighteen pregnant women and three key informants for data collection through individual interviews. Pregnant women who initiated ant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
40
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 23 publications
9
40
0
3
Order By: Relevance
“…Amongst the nine participants, seven stated that they had registered late for their ANC. Registering a pregnancy and booking for antenatal care in the second trimester of pregnancy has been deemed an unsafe practice or attitude by pregnant women; unfortunately, the findings in this study showed that deaf pregnant women often registered late for ANC, in line with the findings of other stud-ies [4,5,[30][31][32]. This study showed that several factors were responsible for the late antenatal registration by deaf pregnant women.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Amongst the nine participants, seven stated that they had registered late for their ANC. Registering a pregnancy and booking for antenatal care in the second trimester of pregnancy has been deemed an unsafe practice or attitude by pregnant women; unfortunately, the findings in this study showed that deaf pregnant women often registered late for ANC, in line with the findings of other stud-ies [4,5,[30][31][32]. This study showed that several factors were responsible for the late antenatal registration by deaf pregnant women.…”
Section: Discussionsupporting
confidence: 82%
“…Unlike the studies which reported that lack of knowledge contributed to late ANC initiation, this study confirmed that deaf pregnant women were knowledgeable about the importance of seeking care and the services offered at antenatal clinics [7,32]. In fact, one of the participants affirmed this with the following statement: "I know that going for antenatal visits is good.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…This study suggests that there is an urgent need to focus on mothers' education. The study also showed the need of advocating primary education for girls not to drop out from school and encourage them to pursue their secondary or higher education is essential in order to attain a tangible change to achieve the maternal and infant mortality reduction of the sustainable development goals through effective implementation of maternal health care services [32,47].…”
Section: Discussionmentioning
confidence: 99%
“…Although physical access has not been reported as a significant problem, utilization is low despite multiple efforts, including demand-side financing projects [ 10 ]. Women’s perceptions of care is a key issue limiting service utilization [ 11 , 12 ]. Women’s negative perceptions of the quality of ANC and the expectation that pregnancy complications are rare may prevent adequate ANC utilization.…”
Section: Introductionmentioning
confidence: 99%